On the origin of epileptic High Frequency Oscillations observed on clinical electrodes. Issue 4 (April 2018) - Shamas, Mohamad; Benquet, Pascal; Merlet, Isabelle; Khalil, Mohamad; El Falou, Wassim; Nica, Anca; Wendling, Fabrice
Highlights: High-frequency oscillations (HFOs) on depth-EEG clinical macroelectrodes originate from non-oscillatory post-synaptic processes. The synchronization level of neuronal populations explains the switch from HFOs to epileptic spikes. Observability of HFOs depends on intracerebral electrode position relative to cortical 3D geometry. Abstract: Objective: In this study we aim to identify the key (patho)physiological mechanisms and biophysical factors which impact the observability and spectral features of High Frequency Oscillations (HFOs). Methods: In order to accurately replicate HFOs we developed virtual-brain/virtual-electrode simulation environment combining novel neurophysiological models of neuronal populations with biophysical models for the source/sensor relationship. Both (patho)physiological mechanisms (synaptic transmission, depolarizing GABAA effect, hyperexcitability) and physical factors (geometry of extended cortical sources, size and position of electrodes) were taken into account. Simulated HFOs were compared to real HFOs extracted from intracerebral recordings of 2 patients. Results: Our results revealed that HFO pathological activity is being generated by feed-forward activation of cortical interneurons that produce fast depolarizing GABAergic post-synaptic potentials (PSPs) onto pyramidal cells. Out of phase patterns of depolarizing GABAergic PSPs explained the shape, entropy and spatiotemporal features of real human HFOs. Conclusions: The terminology "high-frequency oscillation" (HFO) might be misleading as the fast ripple component (200–600 Hz) is more likely a "high-frequency activity" (HFA), the origin of which is independent from any oscillatory process. Significance: New insights regarding the origins and observability of HFOs along depth-EEG electrodes were gained in terms of spatial extent and 3D geometry of neuronal sources.